Adiciones y deducciones tributarias en la determinación del impuesto a la renta y su incidencia en la rentabilidad de la empresa BVCFARMA EIRL año 2017- 2018 - Gutiérrez García, Tiffani Gisell (2019)
One of the components that a company incurs for the generation of its income are the expenses, these are very important when determining the calculation of the income tax, usually the taxpayer himself carries out a process of self-determination, many times In this process, the taxpayer considers that all incurred expenses are necessary to produce income or maintain its production source by incorporating them into the accounting result, the problem that may arise is that at the time of determining the net income some expenses that were considered in this process can be repairable, that is to say when they encounter the administrative and substantial obligation of the presentation and payment of income tax to the treasury, it must be added and / or deducted, determining which of all the expenses applied financially are accepted by the Administration. That is why the present research work has the purpose of determining how the additions and deductions in the determination of the Income Tax affect the Profitability of the company BVCFARMA EIRL 2017-2018. Firstly, an identification and analysis of the additions and deductions that were generated with the development of the company's operations was carried out, followed by the determination of the temporary and permanent differences generated by the additions and deductions, as well as the incidence they generate. in the economic and financial profitability of the company through the use of formulas such as ROE, ROA and profitability ratios, and finally based on the results obtained recommendations were made so that the owner of the company BVCFARMA EIRL can make better decisions. At the end of the present investigation, it was concluded that most of the expenses incurred by the BVCFARMA EIRL company are necessary for the normal development of its operations and for the generation of income, however, these expenses, according to the tax norm are subject to limits or do not comply with certain requirements, thus causing tax repairs and negatively impacting their Profitability, this being the most important and related to the decision making of the company.